GIGI TIRUAN JEMBATAN UNTUK GIGI MOLAR KEDUA RAHANG BAWAH YANG HILANG MELIBATKAN MOLAR KETIGA SEBAGAI GIGI PENYANGGA: FIXED PARTIAL DENTURE FOR THE MISSING MANDIBULAR SECOND MOLAR WITH THE VOLVEMENT OF THE THIRD MOLAR AS ABUTMENT (Dentika: Dental Journal, 2011)
Making fixed partial denture to replace the missing mandibular second molar with the involvement of the third molar as abutment is rarely done, because the location of the 3rd molar is far behind and the narrow space for operator in making the tooth preparation. In addition, the shape and size of crown and root, and position of the 3rd molar in the dental arch does not often encounter the requirement to serve as an abutment. We have made fixed partial denture for a patient who had lost his second lower molar by using the first and third molar as an abutment. The 3rd molar is tilted to mesial along to the lingual aspect more than 25Âº, so we decided to make an intra coronal retainer to the teeth. In line with decreasing the chewing forces, the pontic occlusal surface area, had been made narrow by 20-30%. The result showed that there was no complaint from the patient after the insertion of the dentures. In conclusion, the manufacture of fixed partial denture to replace the missing mandibular second molar with the involvement of the third molar as abutment can be done by considering carefully the principles of biomechanical and preparation.